Palaeopathology and its relevance to understanding health and disease today: the impact of the environment on health, past and present - Roberts, Charlotte Ann (Anthropological Review, 2016)
This paper considers the discipline of palaeopathology, how it has developed, how it is studied, and what limitations present challenges to analysis. The study of disease has a long history and has probably most rapidly developed over the last 40-50 years with the development of methods, and particularly ancient pathogen DNA analysis. While emphasizing that palaeopathology has close synergies to evolutionary medicine, it focuses then on three ‘case studies’ that illustrate the close interaction people have had with their environments and how that has impacted their health. Upper and lower respiratory tract disease has affected sinuses and ribs, particularly in urban contexts, and tuberculosis in particular has been an ever present disease throughout thousands of years of our existence. Ancient DNA methods are now allowing us to explore how strains of the bacteria causing TB have changed through time. Vitamin D deficiency and ‘phossy jaw’ are also described, both potentially related to polluted environments, and possibly to working conditions in the industrial period. Access to UV light is emphasized as a preventative factor for rickets and where a person lives is important (latitude). The painful stigmatizing ‘phossy jaw’ appears to be a condition related to the match making industries. Finally, thoughts for the future are outlined, and two key concerns: a close consideration of ethical issues and human remains, especially with destructive analyses, and thinking more about how palaeopathological research can impact people beyond academia.